2021
DOI: 10.3389/fonc.2021.708900
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Molecular Therapeutic Targets and Their Potential Prognostic Biomarkers Among Kinesin Superfamily of Proteins in Pancreatic Ductal Adenocarcinoma

Abstract: BackgroundKinesin superfamily of proteins (KIFs) has been broadly reported to play an indispensable role in the biological process. Recently, emerging evidence reveals its oncogenic role in various cancers. However, the prognostic, oncological, and immunological values of KIFs have not been comprehensively explored in pancreatic ductal adenocarcinoma (PDAC) patients. We aimed to illustrate the relationship between KIFs and pancreatic ductal adenocarcinoma by using bioinformatical analysis.MethodsWe use GEPIA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Low KIF21B expression indirectly increased the apoptosis and inhibited the proliferation of osteosarcoma cells [ 40 ]. A recent study by Yang et al [ 41 ] also indicated that the overexpression of KIF21B was associated with the immunological and oncogenic pathway activation in pancreatic cancer. Herein, our data highlighted the oncogenic role of KIF21B in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Low KIF21B expression indirectly increased the apoptosis and inhibited the proliferation of osteosarcoma cells [ 40 ]. A recent study by Yang et al [ 41 ] also indicated that the overexpression of KIF21B was associated with the immunological and oncogenic pathway activation in pancreatic cancer. Herein, our data highlighted the oncogenic role of KIF21B in GC.…”
Section: Discussionmentioning
confidence: 99%
“…The kinesin superfamily (KIFs), known as molecular motors with microtubule (MT) class-binding protein superfamily, play pivotal roles in several biological processes, including axonal transport and microtubule stabilization in our body, especially in the brain, that are important for various highly aggressive malignancies including glioma [ 22 ]. Although several compounds targeting mitotic kinesins, including the taxanes, vinca alkaloids, and epothilones, have been successfully used in the treatment of a number of hematologic and solid malignancies, the same efficacy does not appear in glioma patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, KRAS mutation was related to decreased expression of KIF4A in LUAD. In contrast, an analysis of cBioPortal data revealed that KIF4A was upregulated in KRAS -mutant pancreatic ductal adenocarcinoma patient tissues [ 66 ]. It is possible that KRAS might regulate KIF4A in a cell type-specific manner, and this particular regulation in the context of lung cancer requires further elucidation.…”
Section: Discussionmentioning
confidence: 99%